Modulation of miR-181 influences dopaminergic neuronal degeneration in a mouse model of Parkinson's disease - Colleen S. Stein; Jared M. McLendon; Nathan H. Witmer; Ryan L. Boudreau (Elsevier, 2022)
Parkinson's disease (PD) is caused by the loss of dopaminergic (DA) neurons in the substantia nigra (SN). Although PD pathogenesis is not fully understood, studies implicate perturbations in gene regulation, mitochondrial function, and neuronal activity. MicroRNAs (miRs) are small gene regulatory RNAs that inhibit diverse subsets of target mRNAs, and several studies have noted miR expression alterations in PD brains. For example, miR-181a is abundant in the brain and is increased in PD patient brain samples; however, the disease relevance of this remains unclear. Here, we show that miR-181 target mRNAs are broadly downregulated in aging and PD brains. To address whether the miR-181 family plays a role in PD pathogenesis, we generated adeno-associated viruses (AAVs) to overexpress and inhibit the miR-181 isoforms. After co-injection with AAV overexpressing alpha-synuclein (aSyn) into mouse SN (PD model), we found that moderate miR-181a/b overexpression exacerbated aSyn-induced DA neuronal loss, whereas miR-181 inhibition was neuroprotective relative to controls (GFP alone and/or scrambled RNA). Also, prolonged miR-181 overexpression in SN alone elicited measurable neurotoxicity that is coincident with an increased immune response. mRNA-seq analyses revealed that miR-181a/b inhibits genes involved in synaptic transmission, neurite outgrowth, and mitochondrial respiration, along with several genes having known protective roles and genetic links in PD.